Foreign capital and credit market development: The case of Lithuania - Rutkauskas, Aleksandras Vytautas; Dudzevičiūte, Gitana (Journal of Business Economics and Management, 2005)
There have been wide‐ranging discussions on whether the investments of foreign banks into the banking sector of the Central and Eastern Europe countries (CEE) lead to greater competition and increase of the loan portfolio of the banks. Several empirical works have shown that a high proportion of foreign capital in the banking sector of CEE countries has generally positive effects on the quality and amount of loan portfolio of the banking sector, but there may also be some adverse effects. Lithuania has an open economy and the credit market is open to international banking competition. The loan portfolio of the banks in Lithuania was growing very rapidly during the last year. A drop in the loan interest rates was significant and banks offered credits under favourable conditions. At the same time, the Lithuanian banking sector is largely foreign‐owned. Foreign investors currently own approx. 87 % of the share capital of banks in Lithuania. The aim of this paper is to investigate the link between the Lithuanian credit market development and the entry of foreign banks. First published online: 14 Oct 2010